Money Back Warranty on Pricing in Dual Channel Supply Chain (Case Study : Garlick Store Surabaya) - Hilyatun Nuha; Putu Eka Dewi Karunia Wati (School of Industrial and System Engineering, Telkom University, 2018)
The development of internet brings great influence in business management, especially in supply chain. Transaction conducted through the internet in supply chain known e-fulfillment, is an integrated process from receiving customer order, managing transaction, warehousing, managing transportation, communicating, with customer using media of information technology. Online sales concept opens up the researchers to conduct research on online sales and offline sales simultaneously, known Dual Channel Supply Chain (DCSC). One category of products that are sold using this structure is fashion product. However, selling fashion product using DCSC structure it still has shortcomings and challenges. Due to customer can not make a selection, viewing and researching product and quality inspaction product dierctly. Based on this, some enterprises provide product warranty sales system offered. Warranty as a guarantee given to customer to provide security and comfort for making purchases. Warranty gives impact on price of product, both online and offline. This leads to the need to do a calculation the optimum price considering money back warranty. Optimum price obtained in the model demand function using quadratic programming adressing the objective function in the form profit maximum in individual channel (Pw, Ps dan Po) as well as whole profit in DCSC by considering the value of money back warranty (g). The result obatained is optimum price for two scenarios. There are optimum price in individual channel without money back warranty and optimum price in online channel with accomodate money back warranty. Keywords—dual channel supply chain (DCSC); money back warranty; optimization.